2021
DOI: 10.1177/20533691211014741
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of postmenopausal women in rural area, Nepal

Abstract: Background Menopause is one of the natural phenomena in every woman’s life. The transition phase gradually brings lots of changes in the life of women, both physically and mentally. In Nepal, these changes are often viewed as the symptoms of old age. This study aims to determine the prevalence of menopausal symptoms and their quality of life (QOL). Methods A descriptive cross-sectional study was conducted in a rural municipality of Jhapa district, Nepal, with study samples of 215 collected using purposive samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
4
6
0
Order By: Relevance
“…In the psychosocial domain, we found accomplishing less than earlier as a major symptom which is consistent with the findings of a study from Kavrepalanchok [12]. In contrast to our findings, a study from Jhapa, and India reported poor memory as a major symptom [10,11]. A study from Hamadan, Iran found anxiety as a major symptom [9].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the psychosocial domain, we found accomplishing less than earlier as a major symptom which is consistent with the findings of a study from Kavrepalanchok [12]. In contrast to our findings, a study from Jhapa, and India reported poor memory as a major symptom [10,11]. A study from Hamadan, Iran found anxiety as a major symptom [9].…”
Section: Discussionsupporting
confidence: 90%
“…Higher the score higher is the bothersome experience, which is more in our women than in Iran. In the vasomotor domain, we found sweating as a major symptom which is similar to a study from Jhapa and India [10,11]. But in another study from Kavrepalanchok, Nepal, hot flushes was the major symptom [12].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Dietary inflammatory index can trigger inflammatory responses in the body (24, 62) and the inflammatory cytokines are related to low QOL due to physical disability, psychosocial burdens, pain, mood, and sexual function (63)(64)(65)(66)(67)(68)(69)(70)(71)(72) in different conditions and diseases like respiratory tract diseases (24,(73)(74)(75), osteoarthritis and synovitis (76,77), MS (78), obesity (79,80), postmenopausal women (81,82), and hemodialysis patients (83).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the effects of menopause on quality of life is crucial in the treatment of symptomatic postmenopausal women. We can get a more accurate picture of people's emotions and areas of difficulties in comprehending their requirements and health-care distribution by evaluating QOL (Thapa, & Thebe, 2021). Therefore, the current study was conducted to assess the quality of life among post-menopausal women.…”
Section: Introductionmentioning
confidence: 99%